A Descriptive Review of the Prevalence and Usage of Traditional and Complementary Medicine among Saudi Diabetic Patients. (29th August 2018) - Alsanad, Saud; Aboushanab, Tamer; Khalil, Mohammed; Alkhamees, Osama A.
Abstract : Diabetes mellitus represents a major burden in Saudi Arabia where seven million (20% of population) are living with diabetes. This article reviews the literature on usage of traditional and complementary medicine (T&CM) therapies among Saudi diabetic patients, focusing in particular on identifying the prevalence as well as discussing their safety and efficacy. Three databases (PubMed, Cochrane, and ScienceDirect) were searched prior to December 10, 2017, for articles published in peer-reviewed journals that reported primary data on the use of traditional and complementary medicine therapies among diabetic patients in Saudi Arabia. Six studies were selected according to the inclusion/exclusion criteria. In conclusion, the prevalence of use of T&CM therapies among diabetics in Saudi Arabia was 32.18%. This review identified that the most used T&CM therapy among diabetics was herbal treatment. The most used herbs were fenugreek, black seeds, neem, myrrh, helteet, harmel, and aloes. There is insufficient or little evidence to support the efficacy of the most identified herbs and therapies. This review is raising the safety concerns about the used herbs and complementary therapies which were commonly used without any medical consultation.